The correlation between diaphragm thickness, diaphragmatic excursion, and pulmonary function in patients with chronic stroke - Jung, Ju-hyeon (J Phys Ther Sci, 2017)
[Purpose] This study aimed to investigate the correlation between the diaphragm thickness and diaphragm excursion, and pulmonary function in individuals with stroke. [Subjects and Methods] One hundred fourteen patients who were clinically diagnosed with ischemic or hemorrhagic stroke were included. The diaphragm thickness and excursion were assessed using ultrasonography, and the diaphragm thickening ratio was standardized using a formula. To analyze pulmonary function, we measured the forced vital capacity, forced expiratory volume in one second, and peak expiratory flow. [Results] A statistically significant correlation was found between the diaphragm thickness, thickness ratio, and diaphragm excursion; and the forced vital capacity, forced expiratory volume in one second, and peak expiratory flow. [Conclusion] This study demonstrated that there is a relationship between respiratory function and diaphragm thickness and diaphragm excursion, especially in the paretic side of the diaphragm. Therefore, the role of the respiratory muscles of the paretic side is important in rehabilitation programs to improve the respiratory function of stroke patients.